Dead simple - Bloom, Jason; Stern, Daniel, 1957-; Caan, James; Richardson, Patricia, 1951-; Franchise Pictures (Firm); Artisan Home Entertainment (Firm) (Santa Monica, Calif. Artisan Home Entertainment, 2001)
A dark comedy about a small town's attempt to cover up a series of accidental murders.
Videodisc release of the 2000 motion picture.
Director, Jason Bloom ; producers, Demitri Samaha, Tracee Stanley, Josh Miller.
Daniel Stern, James Caan, Patricia Richardson.
DVD.
Closed captioned.
115626
Keywords: Comedy films; Feature films; Films for hard of hearing people